The Effect of Compensation, Job Satisfaction and Work Motivation on Employee Performance at PT Candi Loka Ngawi Regency - Virnanda Cesarila Novanty; Kustini Kustini (Cita konsultindo, 2023)
The purpose of the study was to determine the effect of compensation, job satisfaction and work motivation on the performance of employees of PT Candi Loka. This study uses quantitative methods with a population and sample size of 50 employees, where the sample technique used is a saturated sample. The data collection method was carried out through distributing questionnaires. The data analysis technique used is Partial Least Square (PLS). The results showed that compensation, job satisfaction and work motivation affect employee performance. Keywords: Compensation; Satisfaction; Motivation; Employee Performance